1998
DOI: 10.1126/science.282.5393.1459
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Isotopic Composition of Cenozoic Seawater Sulfate

Abstract: A continuous seawater sulfate sulfur isotope curve for the Cenozoic with a resolution of ϳ1 million years was generated using marine barite. The sulfur isotopic composition decreased from 19 to 17 per mil between 65 and 55 million years ago, increased abruptly from 17 to 22 per mil between 55 and 45 million years ago, remained nearly constant from 35 to ϳ2 million years ago, and has decreased by 0.8 per mil during the past 2 million years. A comparison between seawater sulfate and marine carbonate carbon isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
202
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(211 citation statements)
references
References 47 publications
5
202
0
Order By: Relevance
“…The long-term Cenozoic δ 13 C and δ 34 S records (Zachos et al, 2001;Paytan et al, 1998), when coupled together on the same time scale, strongly suggest that an immense amount of organic carbon without Fe-sulfide minerals accumulated in the late Paleocene (∼60-57 Ma), and a tremendous quantity of Fesulfides accumulated during the early Eocene (∼56-50 Ma). A huge mass of organic carbon placed into peat would provide a high C-low S reservoir, which then might have been "tapped" periodically to cause the PETM (Kurtz et al, 2003) and other negative carbon isotope excursions .…”
Section: Other Hypotheses For Massive Carbon Inputmentioning
confidence: 99%
“…The long-term Cenozoic δ 13 C and δ 34 S records (Zachos et al, 2001;Paytan et al, 1998), when coupled together on the same time scale, strongly suggest that an immense amount of organic carbon without Fe-sulfide minerals accumulated in the late Paleocene (∼60-57 Ma), and a tremendous quantity of Fesulfides accumulated during the early Eocene (∼56-50 Ma). A huge mass of organic carbon placed into peat would provide a high C-low S reservoir, which then might have been "tapped" periodically to cause the PETM (Kurtz et al, 2003) and other negative carbon isotope excursions .…”
Section: Other Hypotheses For Massive Carbon Inputmentioning
confidence: 99%
“…Because barite forms in the water column, seawater elemental distribution patterns can be recorded by authigenic barite. For instance, sedimentary barite has been used to reconstruct the paleocomposition of seawater, including strontium ( 87 Sr/ 86 Sr), oxygen ( 18 O/ 16 O) and sulfur ( 34 S/ 32 S) isotopic compositions (Cecile et al, 1983;Paytan et al, 1993;Martin et al, 1995;Paytan et al, 1998). Attempts to reconstruct the past Nd isotopic composition of seawater ( 143 Nd/ 144 Nd) have also been made (Martin et al, 1995;Paytan, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a comparison between the S and 87 Sr/ 86 S values' compositions of the marine evaporites with the values for contemporaneous seawater [22,26] revealed that most of the sulfate minerals analyzed from these deposits were simply derived from the precipitation of evaporated seawater.…”
Section: Discussionmentioning
confidence: 99%